Good Governance Sebagai Instrumen Kerja Sama Pembangunan Indonesia- Jerman di Yogyakarta - Kusumaningrum, Demeiati Nur (Universitas Muhammadiyah Yogyakarta, 2014)
This research explains the relationship between development cooperation and foreign assistance mechanism. Structural adjustment programs (SAP) required to developing countries for the sake of foreign aid tends to transform into global norm –good governance. Legitimate governance aimed to run accountability, transparency, responsiveness, equity and inclusive, effectiveness and efficiency, rule of law, participatory and consensusoriented. Good governance is realized to strategic partnership of Provincial Government of Yogyakarta and the German Government in the area of administrative reform in 2008. It describes the norm empowerment and elite learning mechanism of good governance at the international structure, domestic-Indonesia, and local-Yogyakarta.